The Relationship Between Lipoprotein (A) And Lipid Profile In Patients Treated With Bay Leaf Extract [Syzygium Polyanthum (Wight) Walp] In Patients Dyslipidemia - Prianwari, Catur; Syafril, Santi (TALENTA Publisher, Universitas Sumatera Utara, 2020)
Background: Increased Lp(a) accelerates atherosclerosis by means of cholesterol deposits in tunica. The purpose of the study was to assess the relationship of decreased Lp(a) with lipid profile in patients with dyslipidemia given bay leaf extract [syzygium polyanthum (Wight) Walp] treatment. Method: Thirty subjects were divided into 2 groups: group I received salam leaf extract therapy 2 x 200 mg and group II received salam leaf extract therapy 2 x 300 mg per day capsules for 30 days randomly selected and double blind. Examination of Lp(a), total cholesterol, LDL-C, HDL-C and TG before and after research. The manufacture of bay leaf extract is done by maseration, the extraction process using ethanol 70%, then the extract is inserted in the capsule. Result: In groups I and II there were significant differences in variable Lp(a) and lipid profiles after treatment except HDL-C. There is a significant correlation between Lp(a) and LDL at salam leaf extract therapy doses of 2x200 mg per day. Conclusion: Decrease in Lp(a) is significantly correlated with decreased LDL-C. Salam leaf extract therapy can predict decreased cardiovascular risk in patients with dyslipidemia.